A nickel-based catalyst with gradient pore structure and its preparation method and application

The laser cladding spraying technology forms a gradient pore structure on the nickel-based catalyst, which solves the problem of poor stability of mesoporous catalysts under high current density, and achieves higher stability and catalytic efficiency.

CN118996488BActive Publication Date: 2025-02-25BAOSHILAI NEW MATERIAL TECHNOLOGY (SUZHOU) CO LTD

Patent Information

Application Number
CN202411479653.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-25
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Existing mesoporous catalysts have poor stability at high current density, are prone to collapse, and are prone to problems such as stress concentration during the preparation process, resulting in insufficient durability.

Method used

Using laser cladding spraying technology, NiAl or NiZn alloy powders of different particle sizes are layered to the surface of the nickel-based substrate to form a nickel-based catalyst with a gradient pore structure, and layer stacking is formed by heat treatment and dealloyment. intermetallic compounds.

Benefits of technology

It improves the stability and service life of the catalyst, enhances the mass transfer rate and catalytic efficiency, and improves the mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118996488B_ABST
    Figure CN118996488B_ABST
Patent Text Reader

Abstract

The present invention relates to a nickel-based catalyst with a gradient pore structure and a preparation method and application thereof. During preparation, a nickel-based substrate is sandblasted and then laser-clad on the surface of the nickel-based substrate by laser cladding of a first alloy powder; then a second alloy powder and a third alloy powder are laser-clad in sequence; finally, a nickel-based catalyst with a gradient pore structure is prepared by heat treatment and dealloying; wherein the first alloy powder, the second alloy powder and the third alloy powder are NiAl alloy powder or NiZn alloy powder; the particle size of the first alloy powder is 1-10µm, and D50 is 3-8µm; the particle size of the second alloy powder is 10-50µm, and D50 is 25-50µm; the particle size of the third alloy powder is 50-100µm, and D50 is 75-110µm. The nickel-based catalyst with a gradient pore structure prepared by the above preparation method can be widely used in the field of hydrogen production by alkaline water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrogen production by alkaline water electrolysis, and in particular to a nickel-based catalyst with a gradient pore structure and a preparation method and application thereof. Background Art

[0002] Porous metal materials usually have the characteristics of high specific surface area, high porosity, good gas and liquid permeability, controllable surface properties, etc., and are widely used in many fields such as filtration and separation, catalysis, energy storage, heat transfer and biomedicine. Gradient porous metal matrix composites are functional materials that control the spatial distribution of each component to make their pore size or porosity present a gradient change. Due to their special gradient structure, they have better performance than homogeneous porous materials, thus meeting the needs of practical engineering applications.

[0003] In the field of hydrogen production by water electrolysis, porous materials usually have better catalytic activity, which is due to the higher specific surface area and material transport channels of porous materials. Currently, commercial Raney nickel electrodes usually have larger pore sizes, from submicron to micron scale, and the improvement of catalytic activity for water electrolysis is limited. Reducing the pore size of Raney nickel to mesopores, such as a few nanometers to tens of nanometers, can provide a larger specific surface and material diffusion channel under the same catalyst mass, and therefore can significantly improve the activity of the catalyst. However, catalysts with mesoporous structures usually have low catalytic stability, especially at higher current densities. This is mainly because the walls of mesoporous catalysts are thin and easily collapsed after being impacted by liquid flow, bubbles, etc., resulting in structural instability. This structural collapse usually starts from the outer layer of the catalyst layer. A more reasonable explanation is that the bubbles generated in the porous inner layer catalyst will overlap with the bubbles generated in the outer layer during the diffusion process to the outer surface, causing volume expansion and a greater impact on the outer layer catalyst. At the same time, the flow of electrolyte also has a greater impact on the outer surface of the catalyst layer. Therefore, for catalyst layers with consistent pore sizes, the outer layer usually collapses first. In addition, since the preparation of mesoporous catalysts usually uses methods such as sacrificial templates, stress concentration and other phenomena are prone to occur, resulting in insufficient durability of the catalyst. Summary of the invention

[0004] The purpose of the present invention is to provide a nickel-based catalyst with a gradient pore structure and a preparation method and application thereof, which solves the problem of poor stability of mesoporous catalysts in the prior art.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a method for preparing a nickel-based catalyst having a gradient pore structure, comprising the following steps:

[0007] (1) sandblasting the nickel-based substrate and cladding the surface of the nickel-based substrate with a first alloy powder;

[0008] (2) cladding the surface of the product of step (1) with a second alloy powder;

[0009] (3) cladding the surface of the product of step (2) with a third alloy powder;

[0010] (4) heat treating and dealloying the product of step (3) to obtain the nickel-based catalyst having a gradient pore structure;

[0011] The first alloy powder, the second alloy powder and the third alloy powder are independently NiAl alloy powder or NiZn alloy powder; the mass ratio of Ni to Al in the NiAl alloy powder is 1-9:1-9, and the mass ratio of Ni to Zn in the NiAl alloy powder is 1-9:1-9;

[0012] The particle size of the first alloy powder is 1-10 μm, the particle size of the second alloy powder is 10-50 μm, and the particle size of the third alloy powder is 50-100 μm.

[0013] Furthermore, the D50 of the first alloy powder is 3-8 μm, the D50 of the second alloy powder is 25-50 μm, and the D50 of the third alloy powder is 75-110 μm.

[0014] Furthermore, in step (1), the nickel-based substrate is any one selected from nickel mesh, nickel felt and nickel foam.

[0015] Furthermore, in step (1), the blasting material used in the sandblasting treatment is any one selected from white corundum, quartz sand and Hainan sand.

[0016] Furthermore, in step (1), the blasting mesh size is 80-120 meshes; the blasting distance is 150-200 mm, the blasting angle is 60-90°, and the blasting gas pressure is 0.5-0.7 MPa.

[0017] Furthermore, the cladding is laser cladding. In step (1), the laser cladding power is 800-2000 W, the nitrogen protective gas flow rate is 5-10 L / min, the spot diameter is 4 mm, the scanning speed is 4 mm / s, and the powder feeding rate is 0.05-0.3 g / s;

[0018] In step (2), the laser cladding power is 1000-2000 W, the nitrogen protective gas flow rate is 5-10 L / min, the spot diameter is 6 mm, the scanning speed is 6 mm / s, and the powder feeding rate is 0.05-0.3 g / s;

[0019] In step (3), the laser cladding power is 1000~3000W, the nitrogen shielding gas flow rate is 5~10 L / min, the spot diameter is 4 mm, the scanning speed is 10 mm / s, and the powder feeding rate is 0.05~0.3g / s.

[0020] Furthermore, in step (4), the heat treatment temperature is 500-800°C, the heat treatment time is 1-2 h, and the cooling rate after the heat treatment is 1-5°C / min.

[0021] Furthermore, in step (4), the dealloying is to place the heat-treated product in an alkaline solution for dealloying, and the concentration of the alkaline solution is 17-30wt%;

[0022] The alkali solution is selected from sodium hydroxide solution or potassium hydroxide solution.

[0023] The second aspect of the present invention provides a nickel-based catalyst with a gradient pore structure, which is prepared by the above-mentioned preparation method.

[0024] The third aspect of the present invention provides an application of a nickel-based catalyst with a gradient pore structure as described above in the field of hydrogen production by alkaline water electrolysis.

[0025] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0026] The present invention adopts a laser cladding and overlapping spraying strategy. First, micron catalyst particles with smaller particle sizes (micron-sized powders of NiAl alloy or NiZn alloy) are laser-clad on a nickel-based substrate; secondly, secondary micron particles are laser-clad and loaded on the coating; finally, micron particles with larger particle sizes are laser-clad again. Subsequently, the nickel-based electrodes are heat-treated to diffuse each other to form stacked layers of intermetallic compounds, which are then combined with dealloying to remove active metal atoms to form a metal laminate material with a gradient porous structure. It has a high mass transfer rate and catalytic efficiency, and has excellent mechanical properties and a long service life. The purpose of the laser cladding and overlapping spraying technology adopted in the present invention is to adhere catalyst particles of different particle sizes to the surface of the nickel-based substrate in a hierarchical manner to form a special gradient porous structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings:

[0028] Figure 1This is a comparison chart of LSV curves of the nickel-based catalyst with a gradient pore structure obtained according to Example 1 of the present invention, the nickel-based catalyst with a uniform porous structure obtained in Comparative Example 5, and the nickel-based catalysts obtained in Example 7, Example 10, Comparative Example 1, and Comparative Example 3;

[0029] Figure 2 The nickel-based catalyst with a gradient pore structure obtained according to Example 1 of the present invention, the nickel-based catalyst with a uniform porous structure obtained in Comparative Example 5, and the nickel-based catalyst obtained according to Example 10 and Comparative Example 1 at 800 mA cm -2 Stability test curve under current density;

[0030] Figure 3 This is a cross-sectional SEM morphology image of a nickel-based catalyst having a gradient pore structure obtained according to Example 1 of the present invention;

[0031] Figure 4 This is a surface SEM morphology image of the nickel-based catalyst with a gradient pore structure obtained according to Example 1 of the present invention at a magnification of 1000 times. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1:

[0034] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof, comprising the following steps:

[0035] (1) A 160 mm × 160 mm nickel mesh was used as a nickel-based substrate, and the surface of the nickel-based substrate was roughened by sandblasting. Specifically, 100-mesh quartz sand was selected, and the sandblasting angle was controlled at 80° and the sandblasting gas pressure was controlled at 0.6 MPa at a distance of 150 mm from the nickel mesh. Subsequently, NiAl alloy powder (Ni: Al=8:2) was fed into the laser beam by laser cladding technology. The laser power was 1600 W, the nitrogen protective gas flow was 5 L / min, the spot diameter was 4 mm, the scanning speed was 4 mm / s, and the powder feeding rate was 0.1 g / s. The nickel mesh that had been sandblasted was clad with the first alloy powder to form a first coating. The particle size of the NiAl alloy powder selected in this step was 5 µm and D50 was 6 µm.

[0036] (2) NiAl alloy powder (Ni: Al=6:4) with a particle size of 30 µm and a D50 of 40 µm was filled into the laser cladding equipment, wherein the laser power was 2000 W, the nitrogen protective gas flow was 8 L / min, the spot diameter was 6 mm, the scanning speed was 6 mm / s, and the powder feeding rate was 0.2 g / s. The second alloy powder was clad at a distance of 120 mm from the surface of the nickel-based substrate to form a second coating;

[0037] (3) NiAl alloy powder (Ni: Al=4:6) with a particle size of 80 µm and D50 of 85 µm was filled into the laser cladding equipment, wherein the laser power was 3000 W, the nitrogen protective gas flow was 10 L / min, the spot diameter was 4 mm, the scanning speed was 10 mm / s, and the powder feeding rate was 0.3 g / s. The third alloy powder was clad at a distance of 130 mm from the surface of the nickel-based substrate to form a third coating;

[0038] (4) The nickel mesh obtained by laser cladding is heat treated in a nitrogen atmosphere at 600°C for 2 h, and then cooled at a cooling rate of 3°C / min; it is then placed in a 20wt% sodium hydroxide solution for dealloying; finally, the dealloyed nickel mesh is taken out, dried and solidified to obtain a nickel-based catalyst with a gradient pore structure.

[0039] Embodiment 2:

[0040] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The only difference between this embodiment and the first embodiment is that the alloy powder selected is NiZn alloy powder, and finally a nickel-based catalyst with a gradient pore structure is prepared.

[0041] Embodiment three:

[0042] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The difference between the embodiment and the first embodiment is that the NiAl alloy powder Ni: Al=7:3 is selected in step (2), and the NiAl alloy powder Ni: Al=3:7 is selected in step (3). Finally, a nickel-based catalyst with a gradient pore structure is prepared.

[0043] Embodiment 4:

[0044] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the NiAl alloy powder selected in step (1) has a ratio of Ni:Al=7:3, the NiAl alloy powder selected in step (2) has a ratio of Ni:Al=5:5, and the NiAl alloy powder selected in step (3) has a ratio of Ni:Al=2:8. Finally, a nickel-based catalyst with a gradient pore structure is prepared.

[0045] Embodiment five:

[0046] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the NiAl alloy powder selected in step (1) has a ratio of Ni:Al=9:1, the NiAl alloy powder selected in step (2) has a ratio of Ni:Al=7:3, and the NiAl alloy powder selected in step (3) has a ratio of Ni:Al=4:6. Finally, a nickel-based catalyst with a gradient pore structure is prepared.

[0047] Embodiment six:

[0048] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the NiAl alloy powder selected in step (1) has a ratio of Ni:Al=6:4, the NiAl alloy powder selected in step (2) has a ratio of Ni:Al=5:5, and the NiAl alloy powder selected in step (3) has a ratio of Ni:Al=2:8. Finally, a nickel-based catalyst with a gradient pore structure is prepared.

[0049] Embodiment seven:

[0050] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The only difference between this embodiment and the first embodiment is that the particle size of the first alloy powder selected is 10 µm, the particle size of the second alloy powder is 50 µm, and the particle size of the third alloy powder is 100 µm. Finally, a nickel-based catalyst with a gradient pore structure is prepared.

[0051] Embodiment eight:

[0052] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The only difference between this embodiment and the first embodiment is that the particle size of the first alloy powder selected is 1 µm, the particle size of the second alloy powder is 10 µm, and the particle size of the third alloy powder is 50 µm. Finally, a nickel-based catalyst with a gradient pore structure is also prepared.

[0053] Embodiment nine:

[0054] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The difference between this embodiment and the first embodiment is that the heat treatment temperature in step (4) is controlled at 500° C., and finally a nickel-based catalyst with a gradient pore structure is prepared.

[0055] Embodiment ten:

[0056] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The difference between this embodiment and the first embodiment is that the heat treatment temperature in step (4) is controlled at 800° C., and finally a nickel-based catalyst with a gradient pore structure is prepared.

[0057] Embodiment eleven:

[0058] This embodiment provides a nickel-based catalyst with a gradient pore structure and a preparation method thereof. The difference between this embodiment and the first embodiment is that the concentration of the sodium hydroxide solution in step (4) is 30 wt %. Finally, a nickel-based catalyst with a gradient pore structure is also prepared.

[0059] Comparative Example 1:

[0060] This embodiment provides a nickel-based catalyst and a preparation method thereof, which is different from the first embodiment only in that the alloy powder selected is NiFe alloy powder.

[0061] Comparative Example 2

[0062] This embodiment provides a nickel-based catalyst and a preparation method thereof, which is different from the first embodiment only in that the particle size of the first alloy powder is 50 µm, the particle size of the second alloy powder is 100 µm, and the particle size of the third alloy powder is 200 µm.

[0063] Comparative Example 3

[0064] This embodiment provides a nickel-based catalyst and a preparation method thereof, which is different from the first embodiment only in that the heat treatment temperature in step (4) is controlled at 1000°C.

[0065] Comparative Example 4

[0066] This embodiment provides a nickel-based catalyst and a preparation method thereof, which is different from the first embodiment only in that the heat treatment temperature in step (4) is controlled at 300°C.

[0067] Comparative Example 5

[0068] This embodiment provides a nickel-based catalyst with a uniform pore structure and a preparation method thereof, and the specific preparation steps are as follows:

[0069] (1) Using the nickel mesh as the substrate, 20wt% sodium hydroxide solution was used to clean it to remove surface stains;

[0070] (2) Using white corundum to sandblast the cleaned nickel mesh for roughening;

[0071] (3) Using plasma spraying equipment, Raney nickel powder (Ni:Al=95:5) was filled into the spraying equipment, wherein the spraying input power was set at 60 kW, the nozzle diameter was set at 0.8 mm, the powder was delivered by nitrogen with a pressure of 0.6 MPa and a flow rate of 10 NLPM, and the spraying was performed at a distance of 120 mm from the surface of the nickel mesh;

[0072] (4) After spraying, the electrode was heat treated at 600°C in a hydrogen atmosphere, and then immersed in a 20 wt% sodium hydroxide solution for 24 h for activation;

[0073] (5) After activation, the nickel mesh is taken out and placed in a well-ventilated environment. After drying and curing, a nickel-based catalyst with a uniform pore structure is obtained.

[0074] The nickel-based catalysts prepared in the above-mentioned embodiments and comparative examples were subjected to performance testing and characterization. The specific test results are listed in the following table:

[0075] Table 1 Performance table of the nickel-based catalysts prepared in Examples 1 to 11 and Comparative Examples 1 to 5 (comparison of stability at different current densities)

[0076]

[0077] It is found from the test results of the embodiments and comparative examples that the performance of the nickel-based catalyst with a gradient pore structure provided in the present invention is significantly better than that of the comparative example.

[0078] from Figure 1 It can be seen that the LSV (linear sweep voltammetry) curves of the nickel-based catalysts with gradient pore structures prepared in Example 1, Example 7 and Example 10 of the present invention, the nickel-based catalysts prepared in Comparative Example 1 and Comparative Example 3, and the nickel-based catalyst with uniform porous structure prepared in Comparative Example 5 were tested by using an electrochemical workstation and a saturated calomel reference electrode.

[0079] The results show that at a current density of 500 mA / cm 2Under the conditions, the overpotentials obtained in Example 1, Example 7, and Example 10 are 63-75 mV lower than the overpotential of the nickel-based catalyst with a uniform porous structure prepared in Comparative Example 5, indicating that the catalytic effects of Example 1, Example 7, and Example 10 are more obvious than those of Comparative Example 5. In addition, the overpotentials obtained in Comparative Example 1 and Comparative Example 3 are 20-43 mV lower than the overpotential of the nickel-based catalyst with a uniform porous structure prepared in Comparative Example 5, indicating that the catalytic effects of Comparative Example 1 and Comparative Example 3 are better than those of Comparative Example 5. In summary, the catalytic effects of Example 1, Example 7, Example 10, and Comparative Example 1 and Comparative Example 3 are better than those of Comparative Example 5.

[0080] like Figure 2 As shown, at 800 mA cm -2 The stability was tested under a high current density. The overpotential decay rate of the nickel-based catalyst with a gradient pore structure was 5-11 µV / h within 1000 hours, while the overpotential decay rate of the nickel-based catalyst with a uniform porous structure provided in Comparative Example 5 was 3-6 times that of the nickel-based catalyst with a gradient pore structure.

[0081] Depend on Figure 3 and Figure 4 As shown, the nickel-based substrate is tightly bonded to the coating, with no obvious cracks and not easy to fall off, ensuring the stability of the electrode. From the figure, it can be observed that the coating has a clear sense of hierarchy, and the nickel-based surface has a clear flaky pore structure accompanied by tiny particles; as the depth of the coating increases, the loose macroporous structure gradually transforms into a dense mesoporous structure.

[0082] In summary, the nickel-based catalyst with a gradient pore structure prepared in the present invention, through laser cladding and spraying technology, adheres catalyst particles of different particle sizes to the surface of the nickel-based substrate in layers to form a special gradient porous structure, which has high mass transfer rate and catalytic efficiency, excellent mechanical properties and long service life.

[0083] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nickel-based catalyst having a gradient pore structure, characterized in that: The following steps are involved: (1) sandblasting the nickel-based substrate and cladding the surface of the nickel-based substrate with a first alloy powder; (2) cladding the surface of the product of step (1) with a second alloy powder; (3) cladding the surface of the product of step (2) with a third alloy powder; (4) heat treating and dealloying the product of step (3) to obtain the nickel-based catalyst having a gradient pore structure; The first alloy powder, the second alloy powder and the third alloy powder are independently NiAl alloy powder or NiZn alloy powder; the mass ratio of Ni to Al in the NiAl alloy powder is 1-9:1-9, and the mass ratio of Ni to Zn in the NiZn alloy powder is 1-9:1-9; The particle size of the first alloy powder is 1-10 µm, the particle size of the second alloy powder is 10-50 µm, and the particle size of the third alloy powder is 50-100 µm; the first alloy powder is micron particles with a smaller particle size, the second alloy powder is secondary micron particles, and the third alloy powder is micron particles with a larger particle size than the second alloy powder; In step (4), the heat treatment temperature is 500-800°C, the heat treatment time is 1-2 h, and the cooling rate after the heat treatment is 1-5°C / min.

2. The method for preparing a nickel-based catalyst having a gradient pore structure according to claim 1, characterized in that: The D50 of the first alloy powder is 3-8 μm, the D50 of the second alloy powder is 25-50 μm, and the D50 of the third alloy powder is 75-110 μm.

3. The method for preparing a nickel-based catalyst having a gradient pore structure according to claim 1, characterized in that: In step (1), the nickel-based substrate is any one selected from nickel mesh, nickel felt and nickel foam.

4. The method for preparing a nickel-based catalyst having a gradient pore structure according to claim 1, characterized in that: In step (1), the blasting material used in the sandblasting treatment is any one selected from white corundum, quartz sand and Hainan sand.

5. The method for preparing a nickel-based catalyst having a gradient pore structure according to claim 4, characterized in that: In step (1), the blasting mesh size is 80-120 meshes; the blasting distance is 150-200 mm, the blasting angle is 60-90°, and the blasting gas pressure is 0.5-0.7 MPa.

6. The method for preparing a nickel-based catalyst having a gradient pore structure according to claim 1, characterized in that: The cladding is laser cladding. In step (1), the laser cladding power is 800-2000 W, the nitrogen protective gas flow rate is 5-10 L / min, the spot diameter is 4 mm, the scanning speed is 4 mm / s, and the powder feeding rate is 0.05-0.3 g / s; In step (2), the laser cladding power is 1000-2000 W, the nitrogen protective gas flow rate is 5-10 L / min, the spot diameter is 6 mm, the scanning speed is 6 mm / s, and the powder feeding rate is 0.05-0.3 g / s; In step (3), the laser cladding power is 1000~3000W, the nitrogen shielding gas flow rate is 5~10 L / min, the spot diameter is 4 mm, the scanning speed is 10 mm / s, and the powder feeding rate is 0.05~0.3g / s.

7. The method for preparing a nickel-based catalyst having a gradient pore structure according to claim 1, characterized in that: In step (4), the dealloying is to place the heat-treated product in an alkaline solution for dealloying, and the concentration of the alkaline solution is 17-30wt%; The alkali solution is selected from sodium hydroxide solution or potassium hydroxide solution.

8. A nickel-based catalyst having a gradient pore structure, characterized in that: The method is prepared according to any one of claims 1 to 7.

9. Application of a nickel-based catalyst with a gradient pore structure as claimed in claim 8 in the field of hydrogen production by alkaline water electrolysis.

Citation Information

Patent Citations

  • Magnesium alloy surface gradient laser cladding layer and preparation technology thereof

    CN106967975A

  • Safe porous nickel catalyst

    CN113042055A

Cited By

  • Hierarchical porous nickel electrode and method for preparing the same

    EP4733445A1